TAKDIR DAN SUNNATULLAH (Suatu Kajian Tafsir Maudhu’i) - Muh. Dahlan Thalib (Al-Ishlah: Jurnal Pendidikan Islam, 2015)
The concept of the Qada and Qadar is still the hot topic of discussion. For Muslims, destiny is a part of faith. Therefore, an understanding of the fate is very important for a Muslim. For an understanding of this destiny will determine the direction and attitude of a Muslim against a variety of things that happened during his life. Therefore, many scholars discuss the concept of destiny in their books. There are three people who understand it differently. The first group; they believe that man is not free at all of destiny because what they do has been determined by God. The second group; they believe that humans are very independent that they do not have any divine intervention at all. The last thought believe that anything done is within the rules of Allah. There is the intervention of God, but humans have a choice to do something.